2003
DOI: 10.1104/pp.102.019042
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Status, Phosphate, and Sucrose Regulate the Expression of Two Plasma Membrane H+-ATPase Genes from the Mycorrhizal Fungus Glomus mosseae  

Abstract: The establishment of the arbuscular mycorrhizal symbiosis results in a modification of the gene expression pattern in both plant and fungus to accomplish the morphological and physiological changes necessary for the bidirectional transfer of nutrients between symbionts. H+-ATPase enzymes play a key role establishing the electrochemical gradient required for the transfer of nutrients across the plasma membrane in both fungi and plants. Molecular analysis of the genetic changes in arbuscular mycorrhizal fungi du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 58 publications
3
80
0
7
Order By: Relevance
“…We suggest that, together with the protons, which are actively transported into the interfacial apoplast by the plant and also by fungal H + -ATPases (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000;Krajinski et al, 2002;Requena et al, 2003;Balestrini et al, 2007), the protons coming from the NH 4 + deprotonation process remain in the interface space and maintain or even reinforce the gradient for H + -dependent transport processes (Fig. 9).…”
Section: Ammonium and Phosphate Uptake At The Interface: A Speculativmentioning
confidence: 98%
“…We suggest that, together with the protons, which are actively transported into the interfacial apoplast by the plant and also by fungal H + -ATPases (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000;Krajinski et al, 2002;Requena et al, 2003;Balestrini et al, 2007), the protons coming from the NH 4 + deprotonation process remain in the interface space and maintain or even reinforce the gradient for H + -dependent transport processes (Fig. 9).…”
Section: Ammonium and Phosphate Uptake At The Interface: A Speculativmentioning
confidence: 98%
“…2b), while GmPMA1 transcripts were detected only in one replicate of the defoliated samples using one-step RT-PCR (data not shown), and not in RT-qPCR. Looking at the data previously reported by Requena et al (2003), GmHA5 showed a very low expression during non-symbiotic growth and a highly induced expression in mycorrhizal roots and in extra-radical hyphae. GmPMA1 was on the contrary more expressed in the pre-symbiosis and less in the late stages of symbiosis, in agreement with our results.…”
Section: Effect Of Defoliation On Am Colonizationmentioning
confidence: 97%
“…To verify the effect of defoliation on AM symbiosis functioning, the expression of fungal genes, for which a previous role during symbiosis was reported, has been evaluated (Requena et al 2003, Balestrini et al 2007, Cappellazzo et al 2008, Gomez-Ariza et al 2009). Due to their role in symbiosis, fungal and plant PT genes are considered as key genes for the symbiosis (Balestrini et al 2007, Bucher 2007.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the well-studied 'Arum'-type interactions, the uptake of phosphorus and minerals occurs at the peri-arbuscular interface, which encompasses the fungal arbuscular membrane, the periarbuscular matrix, and the plant periarbuscular membrane (Gianinazzi-Pearson 1996;Harrison 1999;Parniske 2000). It has been shown that the uptake of phosphorus is energy-dependent, with plant and fungal plasma membrane H + -ATPases as well as a plant phosphate transporter being exclusively localised at the arbuscular interface Ferrol et al 2002;Harrison et al 2002;Requena et al 2003). In contrast to the nutrient uptake by the plant, intraradical hyphae are thought to be responsible for the translocation of carbohydrates to the fungus (Bago et al 2000;Graham and Miller 2005).…”
Section: Introductionmentioning
confidence: 99%